Heart rate and age modulate retinal pulsatile patterns - Ivana Labounková; René Labounek; Radim Kolář; Ralf P. Tornow; Charles F. Babbs; Collin M. McClelland; Benjamin R. Miller; Igor Nestrašil (Communications Biology, 2022)
Video-recordings of retinal pulsatile patterns in human eye are modulated by heart rate and age. This invivo evidence fundamentally impacts modeling of retinal function and clinical design in wide range of medical specialties.